2005
DOI: 10.1086/498023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Severe Malaria in HIV-Infected Adults in South Africa

Abstract: HIV-infected nonimmune adults are at increased risk of severe malaria. This risk is associated with a low CD4+ T cell count. This interaction is of great public health importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 20 publications
9
134
2
6
Order By: Relevance
“…Most of the available data regarding malaria-associated HIV-AIDS is related to the consequences of HIV infection on the degree of anaemia, Plasmodium PD and CD4 + T lymphocyte counts in Pf malaria patients, particularly in sub-Saharan Africa countries (Whitworth et al 2000, Cohen et al 2005, Mouala et al 2009, Davenport et al 2010. However, the impact of both infections on the state of immune cellular activation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the available data regarding malaria-associated HIV-AIDS is related to the consequences of HIV infection on the degree of anaemia, Plasmodium PD and CD4 + T lymphocyte counts in Pf malaria patients, particularly in sub-Saharan Africa countries (Whitworth et al 2000, Cohen et al 2005, Mouala et al 2009, Davenport et al 2010. However, the impact of both infections on the state of immune cellular activation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Plasmodium parasitaemia is most likely related to the impairment of parasite control caused by HIV-1-related immunosuppression (Whitworth et al 2000. Patients with low CD4 + T cell counts of less than 350 cells/mm 3 are more likely to exhibit complications arising malaria (Cohen et al 2005, Mouala et al 2009). Moreover, HIV-1 infection is associated with an increased prevalence of anaemia in Pf malaria (Otieno et al 2006, Davenport et al 2010.…”
mentioning
confidence: 99%
“…Malaria was observed to be endemic in Nigeria and it is the leading cause of morbidity and mortality in the Country (Onwujekwe et al, 2000;FMH, 2001). Cohen et al, (2005) observed an increased prevalence of severe malaria in HIV-infected adults' subjects in South Africa. While Onyenekwe et al, (2007) also observed an increased prevalence of severe malaria in HIV-infected malaria subjects in endemic area of Southern Nigeria.…”
Section: It Is Caused By Human Immunodeficiency Virus (Hiv) (Onyancmentioning
confidence: 91%
“…Presentation of severe malaria has been observed in HIV subjects with CD4 + T cells count less than 2000 x 10 6 cells/ l (Cohen et al, 2005). Onyenekwe et al, (2007) reported a tripled prevalence of malaria infection in symptomatic HIV-infected subjects.…”
Section: It Is Caused By Human Immunodeficiency Virus (Hiv) (Onyancmentioning
confidence: 99%
“…17 Because the control of malaria parasitemia is mediated by the immune system, in theory, severely immunosuppressed HIV-infected patients should have more parasitemia episodes and clinical manifestations. 18 Furthermore, malaria infections have been shown to cause an increase in plasma HIV viral load and to be associated with a more rapid decline in cluster of differentiation 4 (CD4+) cells over time. [19][20][21] HIV disease progression and transmission are strongly associated with blood viral load.…”
Section: Malariamentioning
confidence: 99%